Partial Discharge Characterization of Gaseous Dielectrics for Gas-Insulated Applications - Mohamed Din, Muhammad Iman Aiman; Abd. Rahman, Rahisham (Evolution in Electrical and Electronic Engineering, 2023)
Partial discharge is a localized dielectric breakdown that can harm high-voltage equipment in electrical engineering. It occurs when there is a breakdown of insulation between two conductors under high voltage stress, resulting in sparks or arc flashes. These energetic electrons can age the insulation and lead to equipment failure. The objective of this project is to investigate partial discharge phenomena in gas-insulated systems and measure their intensity. The study refers to previous research to understand the topic and uses ultra-high frequency (UHF) and high-frequency current transformer (HFCT) sensors to measure partial discharge. Measurement circuits were designed for both methods, and MATLAB was used to analyze the partial discharge signals and calculate the pulse charge. The highest pulse charge recorded was 257.46 nC when CO2 was used as the insulation gas, while the lowest was 4.2594 nC with free air as the insulation gas. This indicates that partial discharge is more intense when CO2 is used. In conclusion, conducting partial discharge testing is crucial to assess the condition of high-voltage equipment and prevent failures.